Brain mapping of epileptic activity in a case of idiopathic occipital lobe epilepsy (Panayiotopoulos syndrome) - Leal, A (2007)
The Panayiotopoulos type of occipital lobe epilepsy has generated great interest, but the particular brain areas involved in the peculiar seizure manifestations have not been established. We studied a patient with the syndrome, using high-resolution EEG and simultaneous EEG and functional magnetic resonance imaging (fMRI). Resolution of the scalp EEG was improved using a realistic spline Laplacian algorithm, and produced a complex distribution of current sinks and sources over the occipital lobe. The spike-related blood oxygen level dependent (BOLD) effect was multifocal, with clusters in lateral and inferior occipital lobe and lateral and anterior temporal lobe. We also performed regional dipole seeding in BOLD clusters to determine their relative contribution to generation of scalp spikes. The integrated model of the neurophysiologic and vascular data strongly suggests that the epileptic activity originates in the lateral occipital area, spreading to the occipital pole and lateral temporal lobe.